Mirror energy differences above the 0f7/2 shell: First γ-ray spectroscopy of the Tz = −2 nucleus 56Zn - A. Fernández (Elsevier, 2021)
Excited states in 56Zn were populated following one-neutron removal from a 57Zn beam impinging on a Be target at intermediate energies in an experiment conducted at the Radioactive Isotope Beam Factory at RIKEN. Three γ rays were observed and tentatively assigned to the 6+→4+→2+→0+ yrast sequence. This turns 56Zn into the heaviest Tz=−2 nucleus in which excited states are known. The excitation-energy differences between these levels and the isobaric analogue states in the Tz=+2 mirror partner, 56Fe, are compared with large-scale shell-model calculations considering the full pf valence space and various isospin-breaking contributions. This comparison, together with an analysis of the mirror energy differences in the A=58, Tz=±1 pair 58Zn and 58Ni, provides valuable information with respect to the size of the monopole radial and the isovector multipole isospin-breaking terms in the region above doubly-magic 56Ni.